The influence of transmedia and extra-academic narratives on the formation of the historical culture of high school students - Muñoz-Muñoz, Pablo; Ortuno-Molina, Jorge; Molina-Puche, Sebastian (Frontiers in Education, 2024)
This paper concerns with the importance of traditional and extra-academic sources of knowledge in the configuration of historical culture of Spanish adolescents. To conduct the research, a descriptive phenomenological approach has been designed by analyzing the responses of forty-eight students to a semi-structured interview in which they had to choose 5 characters of contemporary history and indicate the origin of the information. The results show the high coincidence about who are historical significant characters: males and politicians, coincident with other studies conducted in Spain and other countries of the near sociocultural context. The degree of coincidence can be considered as a homogeneous image of the historical culture of the participants. In that sense, there is a high rate of coincidence in the source where this vision of history is mainly generated: the history classroom. The information obtained leads us to confirm the need to reflect on the important stereotypes generated after many decades of formal history teaching with contents far from a necessary critical review. For this reason, it is necessary to reorient the teaching of history to provide a better critical reasoning about how the past is used to understand current societies (ontological perspective) along with how we know about the past (epistemological perspective).